Fibrilação atrial crônica e apnéia obstrutiva do sono - Silva, Betania Braga [UNIFESP] (2009)
Background: Little has been known about the relation of sleep apnea and atrial fibrillation. Recent studies have suggested that the prevalence of atrial fibrillation is increasing in patients with sleep-disordered breathing and it is possible that the sleep apnea contributes to arrhythmogenesis in these patients.We hypothesize that the prevalence of obstructive sleep apnea is higher in chronic atrial fibrillation patients, and the arrhythmia occurrence may be associated to alterations in the sleep patterns. Objectives: To evaluate the prevalence of obstructive sleep apnea, and the sleep respiratory parameters in a sample of chronic atrial fibrillation compared to a sub-sample of the general population. Methods: Fifty-two chronic persistent and permanent atrial fibrillation patients, aged (60.5 } 9.5, 33 males) and 32 control subjects were taken from a sample of an epidemiological study on sleep disorders in the general population of the city of Sao Paulo, Brazil (EPISONO), mean aged 57.3 } 9.6 years old, 15 males. All subjects were evaluated by a staff cardiologist for the presence of medical conditions, and were referred for polysomnography. Results: Considering a cut-off value for apnea hypopnea index . 10 per hour of sleep, the atrial fibrillation group had a higher prevalence of obstructive sleep apnea compared to the control group (81.6% and 60.0%, respectively, p = 0.03). All the oxygen saturation parameters were significantly worse in the AF group, such as: lower oxygen saturation nadir (81.9 } 5.8% and 85.3 } 5.2%, p = 0.01), lower mean oxygen saturation (93.4 } 2.1% and 94.3 } 1.5%, p = 0.02), and longer period of time below 90% (26.4 } 55.8 min and 6.7 } 12.3 min, p = 0.05).There were no differences in age, gender, body mass index, sedentarism, presence of hypertension, type 2 diabetes mellitus, abdominal circumference, systolic and diastolic blood pressure, and sleepiness scoring between groups. Despite similar body mass index, atrial fibrillation patients had a higher neck circumference compared to control group (39.9 } 2.3 cm and 37.7 } 4.5 cm, p = 0.01) and the atrial fibrillation group showed higher percentage time of stage 1 non-REM sleep, superficial sleep (6.4 } 5.9% and 3.9 } 2.6%, p = 0.03). Conclusions: Sleep-disordered breathing is more prevalent in chronic atrial fibrillation patients than in general population subjects. The oxygen saturation parameters and percentage of time spent in superficial sleep were worse in the atrial fibrillation group than in control group. Overall, these data suggest alteration of the cardio respiratory coupling during sleep, in these patients.